PERAN PENDIDIKAN KARAKTER DALAM MENINGKATKAN NILAI, SIKAP, DAN PERILAKU POSITIF GENERASI MUDA UNTUK MEMBENTUK WARGA NEGARA YANG BERTANGGUNG JAWAB: Pendahuluan; Metode Penelitian; Hasil dan Pembahasan; Kesimpulan - Siti Ni’matus Sholikha; Daryono; Shazwany , Fitria; Noviana Bella Donna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the role of character education in shaping positive values, attitudes, and behaviors among youth and its contribution to forming responsible citizens. The study focuses on challenges faced by the younger generation, such as the negative influence of uncontrolled social media, individualism, bullying, and free social interactions, which affect moral development. Using a qualitative approach with library research, the study analyzes relevant literature, including books, journals, and policy documents related to character education and citizenship education. The results show that character education is a strategic effort to instill moral values, ethics, and responsible behavior through integrated learning, habituation, and role modeling. Collaboration among schools, families, and society, as well as the use of digital media, strengthens the internalization of positive values. Effective character education contributes to the development of ethical, disciplined, and socially responsible individuals who understand their rights and obligations as citizens. This study provides both theoretical insights for the development of civic education and practical guidance for strengthening character education in educational and social contexts.